Noise Influence on Damage Detection through Modal State Observers Methodology - Cavalini, A.A.; Franco, V.R.; Gonsalez, C.G.; Lopes Jr., V.; de Melo, G.P (Trends in Computational and Applied Mathematics, 2008)
Noise effect on damage detection methodologies is an important matter. The probability of false diagnosis can be minimized when the noise influence is taken into account. In this paper, the noise effect in the damage detection approach is evaluated using state observers based on modal data. The paper concludes with a numerical application in a plane truss structure considering noise effect in the input signals.